2020
DOI: 10.1177/0361198120909382
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Safety Impact of Protected Intersection Design Elements: A Driving Simulation Approach

Abstract: Protected intersections are used to facilitate safe crossings for non-motorized users. As a relatively new treatment in North America, it is essential to understand how their design elements, such as bicycle intersection-crossing pavement markings and corner refuge island size, enhance bicyclist safety. A driving simulation experiment was developed to test the effectiveness of different design elements of protected intersections on driver speeds. Participants were exposed to different protected intersection de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Literature from the Netherlands ( 52 ) as well other recently published guidelines ( 58 ) highlight the need for intersection treatments in addition to segment-level ones. Such countermeasures could be related to control strategies, for example, bike signals, or to more innovative intersection treatments that eliminate points of conflict between bicyclists and motorists, such as the protected intersection ( 53 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature from the Netherlands ( 52 ) as well other recently published guidelines ( 58 ) highlight the need for intersection treatments in addition to segment-level ones. Such countermeasures could be related to control strategies, for example, bike signals, or to more innovative intersection treatments that eliminate points of conflict between bicyclists and motorists, such as the protected intersection ( 53 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it recommends additional safety analysis at intersections that feature those treatments, to identify safety deficiencies that may responsible for the high predicted crash frequency. Both treatments increase driver awareness of bicyclists’ presence ( 31 , 53 ) and therefore, should continue being implemented. Bike boxes are effective in placing bicyclists in front of motorized vehicles during the red phase so that bicyclists can remain in front when the green phase starts; they also facilitate bicyclists’ turning movements ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results and recommendations of other research and guidebooks for right-turn speed are consistent with this model. A driving simulation study showed that when drivers turn right at protected intersections, whose features include a small turning radius, turning speed at the apex is on average 23 ft/s ( 26 ). The German traffic signals guidelines assume a turning speed of 5 m/s (16.4 ft/s) at signalized intersections when the radius of the inner border of the turning lane is smaller than 10 m (32.8 ft), and otherwise, they assume 7 m/s (23 ft/s) ( 27 ).…”
Section: Recommended Model Parameter Values and Acceleration Profilementioning
confidence: 99%
“…In a study conducted by Bella and Silvestri, a driver’s speed choice was shown to be significantly affected by time-to-zebra arrive, which is defined as the time left to the driver to reach the crossing when the pedestrian arrives at the intersection ( 15 ). Deliali et al conducted a study at protected intersections and showed that drivers significantly reduce speed when performing a right turn in the presence of bicyclists ( 17 ). Minhas et al analyzed both site-based and vehicle-based video recordings and showed that driver behavior was two times safer at signalized intersections ( 18 ).…”
Section: Literature Reviewmentioning
confidence: 99%